Comparison of swimming capacity and energetics of migratory European eel (Anguilla anguilla) and New Zealand short-finned eel (A. australis) - Tudorache, Christian; Burgerhout, Erik; Brittijn, Sebastiaan; van den Thillart, Guido (Frontiers in Physiology, 2015)
The spawning migration of the European eel (Anguilla anguilla) can cover more than 6000 km, while that of the New Zealand short-finned eel (A. australis) is assumed to be approximately 3000 km. Since these species are expected to show adaptive traits to such an important lifetime event, we hypothesised differences in swimming capacity and energetics as a response to this adaptation. In an experimental swimming respirometer set-up, critical swimming speed (Ucrit), optimal swimming speed (Uopt), mass specific oxygen consumption rate (ṀO2), standard metabolic rate (SMR), active metabolic rate at Ucrit (AMRcrit) and at Uopt (AMRopt), the minimum cost of transport at Uopt (COTmin), and the scope for activity, were assessed and compared between the species. With a similar body length and mass, European eels showed ca 25% higher values for both Ucrit and Uopt, and 23% lower values for COTmin, compared to New Zealand short-finned eels. However, SMR, AMRcrit, AMRopt and scope for activity did not differ between the species, indicating very similar swimming physiology traits. This study discusses physiological aspects of long distance migration and provides recommendations for a) swimming respirometry in anguilliform fish, and b) telemetry research using externally attached pop-up tags.